Unpacking Turnover Intention: How Work-Life Balance, Job Satisfaction and Job Embeddedness Matter - Khoiryah, Atifa Zulfa; Soenaria, Syaiful Rahman; Handoyo, Sofik (GoAcademica Research & Publishing, 2025)
Employee performance factors such as work-life balance, job satisfaction, and job embeddedness have an impact on turnover intention. This research aims to see whether the phenomena of PT Telkom's achievements are directly proportional to turnover intention or vice versa. Using quantitative methods by collecting data through questionnaires, the research results show that work-life balance, job satisfaction, and job embeddedness influence turnover intention partially or simultaneously. This study has limitations in the scope of the sample which is limited to PT Telkom employees and does not cover other external variables that can affect turnover intention. For further research, it is recommended that the scope of the sample be expanded by creating clusters for top, middle, and lower management.